Simplified and tessellated mesh for realtime high quality rendering. (February 2016) - Yuan, Yazhen; Wang, Rui; Huang, Jin; Jia, Yanming; Bao, Hujun
Abstract: Many applications require manipulation and visualization of complex and highly detailed models at realtime. In this paper, we present a new mesh process and rendering method for realtime high quality rendering. The basic idea is to send a simplified mesh to hardware pipeline, while use the online tessellation on the GPU to facilitate the rendering of complex geometric details. We formulate it into an inverse tessellation problem that first computes the simplified mesh, and then optimizes the tessellated mesh with geometric details to approximate the original mesh. To solve this problem, we propose a two-stage algorithm. In the first stage, we employ an iterative surface simplification technique, where we take the requirement of hardware tessellation into consideration to obtain an optimal simplified mesh. In the second stage, to better utilize the hardware tessellation, we propose a moving vertex strategy to approximate the tessellated mesh to the original mesh. Results show that our method achieves 2–4 times faster at rendering but still retains high quality geometrical details. Abstract : Graphical abstract: Abstract : Highlights: Mesh simplification and tessellation approach for realtime high quality rendering. Consider factors of fast hardware-tessellation during simplification process. Move tessellated vertices to better approximate geometric features of original mesh. Generate optimal simplified and tessellated mesh under time budget.